Pre-suppression Jesuit Activity in the British Isles and Ireland Brill's Research Perspectives in Jesuit Studies - McCoog, Thomas M. (Brill Research Perspectives in Humanities and Social Sciences, 2019)
Conceived in optimism but baptized with blood, Jesuit missions to the British Isles and Ireland withstood government repression, internal squabbles, theological disputes, political machinations, and overbearing prelates to survive to the Society's sSuppression in 1773 and beyond.; Readership: All interested in the internal and external struggles of Roman Catholics in early modern Great Britain and Ireland, and especially with Jesuit attempts to adapt their way of life to the demands of the mission.